Pengaruh Nilai Tukar Rupiah dan Tingkat Suku Bunga terhadap Indeks Harga Saham Gabungan melalui Tingkat Inflasi di Indonesia - Hario Aji Hartomo; Ismail Razak; Munawaroh (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to analyze the effect of exchange rate and interest rate on composite stock price index through inflation rate in Indonesia. The research method used is quantitative research with descriptive analysis, classical assumption test analysis, multiple linear regression analysis and path analysis with mediation. The results of the study show that: 1) Exchange rate has a significant negative effect on composite stock price index; 2) Interest rate also has a significant negative effect on composite stock price index;3) Inflation has a significant positive effect on composite stock price index; 4) Inflation significantly mediates the effect of exchange rate and interest rate on composite stock price index.